2013
DOI: 10.1063/1.4798233
|View full text |Cite
|
Sign up to set email alerts
|

Reducing thickness dependence of critical current density in GdBa2Cu3O7-δ thin films by addition of nanostructured defects

Abstract: The effect of incorporating nanostructured defects in a form of BaSnO3 (BSO) nanorods on the thickness dependence of critical current density (Jc) in GdBa2Cu3O7-x (GdBCO) thin films was investigated. Pure and 2 wt. % BSO-doped GdBCO films were fabricated by the pulsed laser deposition with the thicknesses t of both films increasing from 0.2 μm to 1.5 μm. The magnetization data measured at 77 K with the field being applied parallel to the c-axis of the films showed two important improvements. First, the Jcs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…The thickness dependence of J c for our IBS CCs is quite different from that in cuprate superconductors. It has been found that the J c - t behavior in cuprate superconductors can be addressed by collective pinning theory, by which the J c reduction with increasing thickness can be well described as J c ∼ t −1/2 , followed by a crossover thickness t c , over which J c becomes almost thickness independent ( Wang and Wu, 2007 ; Tran et al., 2013 ; Gurevich, 2007 ). It is interesting to note that the thinnest films with the lowest T c showed the highest J c up to 5 T for H//c and 9 T for H//ab .…”
Section: Resultsmentioning
confidence: 99%
“…The thickness dependence of J c for our IBS CCs is quite different from that in cuprate superconductors. It has been found that the J c - t behavior in cuprate superconductors can be addressed by collective pinning theory, by which the J c reduction with increasing thickness can be well described as J c ∼ t −1/2 , followed by a crossover thickness t c , over which J c becomes almost thickness independent ( Wang and Wu, 2007 ; Tran et al., 2013 ; Gurevich, 2007 ). It is interesting to note that the thinnest films with the lowest T c showed the highest J c up to 5 T for H//c and 9 T for H//ab .…”
Section: Resultsmentioning
confidence: 99%
“…As the drive for performance and complexity of electronic and optical devices increases, new materials with novel functionalities and multifunctionalities are highly desired [1,2]. Nanocomposite thin film materials and nanoparticles are considered some of the most promising options given their advantages in both size and physical property tunability when compared to traditional single phase films [3][4][5][6][7][8][9][10]. Nanocomposite thin film materials consist of three main different nanostructure types: multilayers, nanoparticles-in-matrix, and vertically aligned nanocomposites (VANs) [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…A/cm-w から 124.7A/cm-w(77 K, 1 T)に向上した。 Fig. 16 Field dependence of Ic in a 3.0 m-thick, BHO-doped YBCO film.…”
unclassified